Nucleocapsid as a next-generation COVID-19 vaccine candidate. (September 2022) - Oronsky, Bryan; Larson, Christopher; Caroen, Scott; Hedjran, Farah; Sanchez, Ana; Prokopenko, Elena; Reid, Tony
Highlights: Currently approved COVID-19 vaccines contain spike protein Spike protein is vulnerable to mutation, which may compromise vaccine efficacy Despite the protection against severe symptomatic disease afforded by spike-based mRNA vaccines and by less-immunogenic inactivated virus vaccines, waning immunity over time, predisposing patients to reinfection, has been demonstrated Nucleocapsid protein is less prone to mutation Including nucleocapsid in future vaccine boosters as homologous prime-boost or as a heterologous prime-boost in combination with spike-based vaccines may provide improved protection Abstract: Multiple new variants of the SARS-CoV-2 virus have emerged globally, due to viral mutation. The majority of COVID-19 vaccines contain SARS-CoV-2 spike protein, which is susceptible to mutation. It is known that protection against COVID-19 after two doses of mRNA vaccine continuously wanes over time. If viral variants contain mutated spike protein, current vaccines may not provide robust protection. This perspective suggests the inclusion of SARS-CoV-2 nucleocapsid protein in future COVID-19 vaccines and boosters, as nucleocapsid is much less vulnerable to mutation and may provide stronger immunity to novel viral variants.